Systemic inflammatory response index improves prognostic predictive value in intensive care unit patients with sepsis - Tuo Xu; Shuaiwei Song; Ke Zhu; Yin Yang; Chengyu Wu; Naixue Wang; Shu Lu (Scientific Reports)
Abstract Sepsis is a severe infectious disease with high mortality. However, the indicators used to evaluate its severity and prognosis are relatively complicated. The systemic inflammatory response index (SIRI), a new inflammatory indicator, has shown good predictive value in chronic infection, stroke, and cancer. The purpose of this study was to investigate the connection between sepsis and SIRI and evaluate its predictive usefulness. A total of 401 patients with sepsis were included in this study. Multiple linear regression and logistic regression analyses were performed to evaluate the relationship between SIRI and sepsis. The restricted cubic spline (RCS) method was employed to illustrate the dose-response relationship. The area under the curve (AUC) and decision curve analysis (DCA) were used to evaluate the prognostic value of SIRI. Multiple linear regression analysis revealed a significant positive correlation between SIRI and both blood cell count and Sequential Organ Failure Assessment (SOFA) score. Additionally, higher SIRI levels were significantly linked to a higher risk of sepsis worsening, according to logistic regression analysis. The RCS curve demonstrated that the risk of poor prognosis rose with increasing SIRI, particularly when SIRI exceeded 6.1. Furthermore, AUC and DCA results showed that SIRI had superior predictive value compared to traditional indicators. A higher SIRI is linked to a worse prognosis and more severe sepsis. SIRI may serve as a novel prognostic indicator in sepsis, though further clinical studies are necessary to confirm these findings.